Democracy and the anti-asylum struggle: images of an unceasing dispute - Medeiros Amado, Lais; Hausen Mizoguchi, Danichi (Argumentum, 2020)
In contemporary Brazilian politics the suspension of rights threatens the achievements of the anti-asylum movement. Paying attention to the prevailing context and the consequent weakening of collective and militant practices, this article reflects on disputes involving the State, democracy and the anti-asylum struggle and explores ways of confronting the current situation. To do so, we start from the experiences of a psychology student, her first internship, her later work in the mental health network, and her experiences of the anti-asylum movement. Combining the thoughts of authors such as Gilles Deleuze, Judith Butler and Suely Rolnik, we conclude that the pathways linked to the occupation of the city are essential ways of confronting the devaluation of life and the stigma of mental illness. Keywords: Democracy. Anti-asylum Struggle. City.